Anatomical study of Momordica charantia L. from Bangladesh (Dhaka University Journal of Biological Sciences, 2018)
Recent investigation on the root, stem, leaf and petiole anatomy of Momordica charantia L. completed the detailed anatomical study of the genus Momordica from Bangladesh. Root has tetrach vascular bundles where thick patches of sclerenchyma cells encompassed the vessel cells. Five angular ridges and furrows are visible through stem transverse section typical to Cucurbitaceae. Total nine open, bicollateral fibro-vascular bundles are observed in stem crosssection where three large are in the center and others each are under the ridges. Midrib of the leaf is characterized by several double and scarcely seated stalkless globular cystoliths in the lower epidermis. Configuration of petiole is octagonal in shape with eight ridges where seven fibro vascular bundles situated as a ring. Stem and leaf has multicellular, unisireate blunt ended conical shaped trichomes where petiole has similar trichomes with both blunt and pointed head.Dhaka Univ. J. Biol. Sci. 27(1): 69-74, 2018 (January)